AN ANALYSIS OF TRANSITIVITY SYSTEM IN MEMOIRS WRITTEN BY EFL STUDENTS - Riyan Wahyuni; Hamzah Hamzah; Delvi Wahyuni (English Language and Literature, 2019)
Although there have been many studies about the language style of the writer in many kinds of writing, but there are few studies found in analyzing language style towards EFL students’ writing. This study is intended to investigate stylistics of EFL students writing. The purpose of this study is to identify the linguistic choices by investigating transitivity system of process types, participants, and circumtantial elements that characterize EFL student’s writing in memoirs. The analysis in this study is based on Halliday and Matthiessen’s (2004) theory of ideational metafunction. This research used descriptive method. The data consist of 950 clauses that were obtained from 15 texts of memoir written by English Department student of State University of Padang in West Sumatera. The finding shows the students’ texts consist of processes, participants and circumstantial elements which fulfill the linguistic features in carrying meaning. The study has found that material process (338 data) is placed as the most dominant process types found in student’s writing. Then participant of human (916 data) is found as the most dominant one in student’s writing. And for circumstantial element, the circumstance of location (183) is found with the highest percentage in student’s memoir.